2016
DOI: 10.1371/journal.pone.0155498
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk Factors for Recent HIV Infection in Kenya Using a Recent Infection Testing Algorithm: Results from a Nationally Representative Population-Based Survey

Abstract: IntroductionA recent infection testing algorithm (RITA) that can distinguish recent from long-standing HIV infection can be applied to nationally representative population-based surveys to characterize and identify risk factors for recent infection in a country.Materials and MethodsWe applied a RITA using the Limiting Antigen Avidity Enzyme Immunoassay (LAg) on stored HIV-positive samples from the 2007 Kenya AIDS Indicator Survey. The case definition for recent infection included testing recent on LAg and havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…This is consistent with HIV risk factor analysis reported previously34. Two recently published studies also identified history of STI as a risk factor for recent HIV infections in both rural western Kenya and the country as a whole1625. Prompt diagnosis and treatment of STIs, accompanied with risk reduction counselling remain vital to the success of HIV prevention initiatives in this setting.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is consistent with HIV risk factor analysis reported previously34. Two recently published studies also identified history of STI as a risk factor for recent HIV infections in both rural western Kenya and the country as a whole1625. Prompt diagnosis and treatment of STIs, accompanied with risk reduction counselling remain vital to the success of HIV prevention initiatives in this setting.…”
Section: Discussionsupporting
confidence: 87%
“…This is one of the few applications of a multifactorial strategy and the recent approaches and recommendations for cross-sectional HIV incidence testing algorithms in Africa1617. We optimised an MAA that identified potential recent HIV infections in the study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay, described elsewhere, has been previously applied in national household surveys in South Africa and Kenya [1011]. The assay tested for the presence of nevirapine, efavirenz, lamivudine, and lopinavir which were included as one or more drugs in the national standardized first-line or second-line ARV regimens at the time of the survey [12].…”
Section: Methodsmentioning
confidence: 99%
“…[ 7 9 ] Self-reported treatment for an STI in the preceding 12 months was associated with a 200% increased likelihood of recent HIV infection in a population-based survey in Kenya. [ 10 ] Sexual health services in the United Kingdom and elsewhere have been successfully used as a platform to identify high-risk individuals for pre-exposure prophylaxis and rapid initiation of antiretroviral therapy (ART) and this has contributed to declines in new HIV diagnoses. [ 11 , 12 ]…”
Section: Introductionmentioning
confidence: 99%